Respuesta :
Answer:
y = 4
Step-by-step explanation:
We have to use the distributive property. Remember that the distributive property states that when expanding out a parentheses, you must find the sum of the product of the "outside term" with each of the "inside terms".
In this case, the "outside term" is 3 and the "inside terms" are y and 4. So, we need to multiply 3 by each of y and 4 and then add those together:
3(y + 4) = 24
3 * y + 3 * 4 = 24
3y + 12 = 24
Now, we subtract 12 from both sides to isolate the variable:
3y + 12 - 12 = 24 - 12
3y = 12
Finally, divide by 3 from both sides to get y alone:
3y/3 = 12/3
y = 4
Thus, y = 4.
Hope this helps!
Answer:
y = 4
Step-by-step explanation:
3(y+4) = 24 <- This is a linear equation so its solved as such
3y+12 = 24 <- Distribute the (PEMDAS)
-12 -12 <- Get y alone
3y = 12 <- Rewrite with y alone
[tex]\frac{3y}{3}[/tex] = [tex]\frac{12}{3}[/tex] <- Divide both sides
y = 4